L'indexation des pensions alimentaires - Gervais, Denise (Les Cahiers de droit, 1978)
The rise in the cost of living has worsened the alimentary creditor's plight. Given the present economic context, the creditor's claim, which is supposed to provide him with the basic essentials, has fallen in value and no longer adequately serves its purpose. This study draws up an inventory of possible solutions to remedy the situation, such as the indexing of alimony.